Influence of the synthesis parameters on the transport properties of Mg2Si0.4Sn0.6 solid solutions produced by melting and spark plasma sintering. (April 2022) - Assahsahi, Ilhame; Popescu, Bogdan; Enculescu, Monica; Galatanu, Magdalena; Galca, Aurelian-Catalin; El Bouayadi, Rachid; Zejli, Driss; Galatanu, Andrei
Abstract: In this work, the influence of the preparation route on the structural, morphological, and thermoelectric properties of the Mg2 Si0.4 Sn0.6 solid solutions is investigated. The synthesis based on melting the constituent elements in a closed graphite crucible followed by spark plasma sintering allows mixing elements with a large difference of their melting temperatures and a good control of sample stoichiometry. The optimized synthesis route is validated by the doped V and Sb samples, which yield good thermoelectric performance. The n-type doping leads to two orders of magnitude increase of the carrier concentration, and thus a subsequent increase of the electrical conductivity, which, in turn, augments greatly the power factor of the Mg1.98 V0.02 Si0.385 Sn0.6 Sb0.015 to 42.61 x10 −4 Wm −1 K −2  at 650K. Although doping slightly enlarges the thermal conductivity, a peak value of the figure of merit ZT∼1.15 is obtained at 723K, which is 20 times higher than the ZT of un-doped material. Highlights: Mg2 Si0.4 Sn0.6 is synthesized by melting in closed graphite crucible and sintering. SEM/EDX-mapping and Raman spectroscopy provide better insight of phase separation. Elements with high melting temperature can be used as dopants. V and Sb doping yields a peak value of the figure of merit, ZT, ∼1.15 at 723K.